Determination of tetracycline residues in animal tissues by thin-layer chromatography - H. Ahmet ACET; Ömer DEMET; Bünyamin TRAŞ (Eurasian Journal of Veterinary Sciences)
This study was evaluated to determine by thin layer chromatography of their residues to !be found in animal tissues of tetracycline group antibiotics, which were widely used in Veterinary field.